The mediating effect of coping styles between self-compassion and body image disturbance in young breast cancer survivors: a cross-sectional study - Fei Zhu; Chunlei Liu; Wan Zhang; Wanmin Qiang; Xiaoping Yin; Qian Lu (BMC, 2023)
Abstract Background Young breast cancer survivors with body image disturbance have poor quality of life. Self-compassion and different coping styles can influence their body image. The purpose of the study was to investigate the relationship between self-compassion, coping styles, and body image disturbance, and examined the mediation role of coping styles between self-compassion and body image disturbance among young breast cancer survivors in China. Methods In the cross-sectional study, a total of 310 young women with breast cancer were assessed on self-compassion, coping styles, and body image disturbance by self-reported questionnaires in China. Spearman's correlation was used to test the links between variables and to verify the indirect effects between variables by constructing a structural equation model. Results There were correlations between self-compassion, different coping styles, and body image disturbance. Confrontation, avoidance, and acceptance-resignation coping had significant mediation effects on the association between self-compassion and body image disturbance. The mediation effects of confrontation coping were greater than avoidance, and acceptance-resignation coping. Conclusions In this study, different coping styles acted as mediators between self-compassion and body image disturbance, providing support for further understanding the mechanism between self-compassion and body image disturbance, and developing comprehensive interventions for body image disturbance. Oncology nurses should pay attention to the breast cancer survivors' self-compassion and coping styles and encourage them to adopt adaptive coping strategies, which can reduce body image disturbance.